Risk Factors Associated with Neonatal Mortality among Premature Newborns Admitted to a Neonatal Care Unit in Botswana: A Prospective Observational Study - Alemayehu Mekonnen Gezmu; Endale Tefera; Sajini Souda; Aone Ditirwa; Kagiso Mochankana; Britt Nakstad (Journal of Global Antimicrobial Resistance)
Background: Sub-Saharan Africa accounts for 28% of the global burden of neonatal mortality. This study aimed to investigate mortality risk and associated factors in premature newborns in a neonatal care unit in Botswana. Method and materials: Data collected prospectively on 418 premature newborns at a referral hospital in Botswana. Univariate analysis identified potential risk factors, and multivariate logistic regression controlled for confounders. Adjusted odds ratios (aOR) with 95% confidence intervals (CI) were estimated, and statistical significance was set at p < 0.05. Result: There were 52.6% males, 81.6% born in the same facility. Mean birth weight was 1448.7 grams (±454), and mean gestational age was 31.3 weeks (±3.2 weeks). Very premature neonates (<32 weeks) accounted for 61.2%, while 51.9% had very low birth weight (<1500 grams). Most common diagnosis was sepsis (79.9%), followed by respiratory distress syndrome (RDS), hypothermia, and hypoglycemia. Neonatal mortality rate was 21.5%.Associated factors were very low birth weight (aOR 5.62, 95% CI 2.43-12.99), 5th minute Apgar score < 5 (aOR 8.32, 95% CI 3.68-18.22), vaginal delivery (aOR 3.57, 95% CI 1.60-7.93), no enteral feeding (aOR 9.17, 95% CI 3.35-25.08), shock (aOR 12.99, 95% CI 2.33-72.35), pulmonary hemorrhage (aOR 34.30, 95% CI 8.01-146.8), RDS (aOR 5.46, 95% CI 2.18-13.71), hypothermia (aOR 3.58, 95% CI 1.35-9.50), apnea of prematurity (aOR 2.36, 95% CI 1.03-5.39), neonatal seizure (aOR 7.83, 95% CI 1.49-41.05), and grade 3 Hypoxic ischemic encephalopathy(HIE) (aOR 7.57, 95% CI 1.08-52.77). Conclusion: This study highlights the need for targeted interventions to improve neonatal care in Botswana.